DOES WORK–LIFE BALANCE REDUCE TURNOVER INTENTION? JOB STRESS MEDIATION AMONG PLANTATION EMPLOYEES - Irena Cyntia Dewi Putri; Meiske Claudia (International Journal of Multidisciplinary Reseach, 2026)
This study examines the effect of Work–Life Balance (WLB) on Turnover Intention by investigating the mediating role of Job Stress among plantation employees. A quantitative approach with an explanatory survey design was employed. Data were collected from 135 permanent employees using purposive sampling and analyzed through Structural Equation Modeling–Partial Least Squares (SEM–PLS) with SmartPLS. The findings demonstrate that Work–Life Balance has a negative and significant effect on both Job Stress and Turnover Intention. In contrast, Job Stress exerts a positive and significant effect on Turnover Intention. Furthermore, Job Stress partially mediates the relationship between Work–Life Balance and Turnover Intention, indicating that employees who experience a better balance between their work and personal lives are less likely to experience job stress, which subsequently lowers their intention to leave the organization. These findings underscore the importance of promoting work–life balance as an organizational strategy to alleviate job stress and strengthen employee retention. This study also extends the employee retention literature by providing empirical evidence that Job Stress represents an important mechanism through which Work–Life Balance influences Turnover Intention in the plantation industry.